SPATIAL DECISION SUPPORT SYSTEM FOR LIVELIHOOD PROGRAMMES IN NORTHERN NIGERIA (FUDMA JOURNAL OF SCIENCES, 2021)
The paper examines the relevance of geospatial maps and technics in execution of livelihood support projects among rural poor.  Previous attempts towards driving the poor along prosperity pathways in Nigeria have failed because of incorrect deployment of interventions in time and space. Global positioning systems and Geographical information systems were employed in this study to provide insight to the challenges faced by previous livelihood support projects in the country while also providing a robust spatial decision support system for geographical targeting of interventions to vulnerable households. The study selected 1,459 households from the 42,000 households adopted for the Feed the Future Project in 3 northern States namely; Sokoto, Kebbi States and the Federal Capital Territory. Acquired survey data were converted into GIS maps so as to expose hidden trends in the characteristics of target population and to suggest the best options for interventions. The data were subjected to spatial analysis such as simple distance analysis. The outcomes revealed 86% of sampled households to be largely below the poverty line. This is mainly due to poor access to facilities like health care, markets, good roads, agricultural inputs, agricultural information and advisory services. 10 % of childrenâ€™s absolute score of Mid Upper Arm Circumference (MUAC) revealed acute malnutrition. 42 % of the household however now have stronger safety nets as a result of the interventions. The study found Spatial Information technology highly useful in social intervention project as the one by the Feed the Future project
Keywords: Livelihood support, Wealth ranking, Spatial Information Systems, Northern Nigeria